Assessing public transit service equity using route-level accessibility measures and public data. (February 2018) - Karner, Alex
Abstract: The benefits and burdens of public transit service changes can be quantified using many different metrics. In the United States, the Federal Transit Administration requires transit agencies to assess the equity of proposed service changes using the demographic shares of affected riders. The purpose of the work presented here is to inform the development of more robust transit equity analyses than are currently conducted by integrating measures of accessibility – the ease with destinations can be reached – into FTA-required analyses. The measures are calculated using publicly available data, including the US Census Bureau's Longitudinal Employer-Household Dynamics dataset and transit route and schedule information in the General Transit Feed Specification (GTFS) format. The results demonstrate that relying on a single measure (e.g. population shares or accessibility) to associate a route with a particular demographic group is likely to be deficient. Previous academic work on accessibility has not translated well to practice in part because the calculation of accessibility relied upon regional travel demand model outputs that were difficult to obtain. This work thus fills an important gap in the literature and practice by tying advances in the academic literature to FTA-mandated analysis with publicly available data.